A festival of the fishing communities - Mumbai Archive Project Team (Jio Institute, 2024)
Narali Purnima is celebrated by fishing communities living along the western coastline of India, particularly in Maharashtra and Gujarat. In Mumbai, the Koli community celebrates Narali Purnima in places like Versova Koliwada (pictured), among other fishing villages.